Область збіжності перетворення Ейлера степеневого ряду аналітичної функції - Сухорольський, М.А. (Український математичний журнал, 2008)
Рассмотрено преобразование Эйлера степенного ряда аналитической функции, являющегося ее разложением в ряд по системе полиномов. Исследована область сходимости преобразования в зависимости от параметра преобразования и характера особых точек функции. Показано, что преобразование продолжает функцию за пределы круга сходимости ее ряда на отрезке границы между двумя особыми точками функции. В частности, установлено, что степенной ряд функции, особые точки которой находятся на одном луче, суммируется преобразованием в полуплоскости. We consider Euler’s transformation of power series of an analytic function, which is its expansion into a
series in system of polynomials. We investigate the domain of convergence of the transformation
depending on the parameter of transformation and the character of singular points of the function. We
show that the transformation extends the function beyond the boundary of the circle of convergence of
its series on the boundary interval between two singular points of the function. In particular, we
establish that the power series of the function whose singular points are located on the same beam is
summarized by the transformation in a half-plane.